2023
DOI: 10.1101/2023.03.18.23287442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Diet on the Gut Microbiome, Mood and Happiness

Abstract: The gut microbiome may be both helpful and harmful, and not only is it affected by diet, it has also been shown to affect mental health including personality, mood, anxiety and depression. In this clinical study we assessed dietary nutrient composition, mood, happiness, and the gut microbiome in order to understand the role of diet in the gut microbiome and how that affects mood and happiness. For this pilot study, we enrolled 20 adults to follow this protocol: recording a 2-day food log, sampling their gut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Based on the data analysis, it was concluded that following a vegetarian diet was associated with a reduced risk of developing depression. In the same year, a pilot study was conducted on 20 people assessing the relationship between mood, diversity of intestinal microbiomes and type of diet [31]. The Depression Anxiety Stress Scale (DASS-42),…”
Section: The Impact Of a Vegetarian Diet On Mood -Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the data analysis, it was concluded that following a vegetarian diet was associated with a reduced risk of developing depression. In the same year, a pilot study was conducted on 20 people assessing the relationship between mood, diversity of intestinal microbiomes and type of diet [31]. The Depression Anxiety Stress Scale (DASS-42),…”
Section: The Impact Of a Vegetarian Diet On Mood -Research Resultsmentioning
confidence: 99%
“…The collected literature review shows that a vegetarian diet seems to be a promising measure, helpful in reducing the risk of depressive disorders and the severity of anxiety, and has a positive impact on mood and holistically understood mental health [4,[25][26][27][28][29][30][31]. In turn, there are studies that have shown a correlation between the consumption of highly processed unhealthy food and the severity of depressive symptoms and anxiety, but no significant effect on mood was observed in the case of a plant-based diet [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Higher emotional motivation in situations of depression, stress, and boredom can result in eating as a form of emotional comfort [ 94 ]. Conversely, consuming carbohydrate-rich foods can alleviate stress by increasing serotonin levels, positively affecting mood [ 100 , 101 ].…”
Section: Changes In Consumer Buying Behavior In the Face Of The Covid...mentioning
confidence: 99%
“…One exciting area of research that unites discussions of folate and omega-3 fatty acids is the relationship between gut microbes and mental health. Since the development of the first scientific frameworks linking non-pathogenic microbes with mental health and cognition, in the early 2000s [65,66], it has become increasingly clear that the gut microbiome plays an important role in neuropsychiatry [67,68]. There are multiple mechanisms by which gut microbes can influence brain and behavior.…”
Section: Gut-brain-microbiome Linksmentioning
confidence: 99%